Analysis of Mobility Patterns to Oklahoma Food Banks During the SARS-COV-2 Pandemic - Madison R. E. Swayne; Bryce C. Lowery; Halley Reeves; Nicole Dundas (Findings, 2023)
We investigate changes in travel to food banks during the outbreak of SARS-CoV-2. The pandemic created challenges that impacted the availability of food and the ability of individuals to access food -- increasing demand on food banks. In a context where face-to-face interactions were not possible, we use cell phone mobility data to evaluate changes in food bank utilization during this period of increased demand for services. From 2017 to 2019 there were an increasing number of trips to food banks from a closer set of census block groups. In 2020 overall trips decreased but travel distances to food banks increased.